2019
DOI: 10.1002/pc.25208
|View full text |Cite
|
Sign up to set email alerts
|

Enhancing thermal conductivity and near‐infrared radiation reflectance of poly(ε‐caprolactone)/poly(lactic acid)‐based nanocomposites by incorporating hexagonal boron nitride

Abstract: This work aims to develop multifunctional biodegradable ternary nanocomposites with heat dissipation capability. The effects of adding hexagonal boron nitride (hBN), regarding phase morphology, near-infrared radiation (NIR) reflectance and thermal conductivity of poly (ε-caprolactone) (PCL) and poly(lactic acid) (PLA) blends were investigated. The hBN nanoparticles were selectively localized in the PCL phase. Scanning electron microscopy showed that the increased hBN concentration in the PCL/PLA blend led to a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
24
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(25 citation statements)
references
References 51 publications
(76 reference statements)
1
24
0
Order By: Relevance
“…In our previous studies with ternary systems, we observed that TiO 2 was selectively localized at the PCL/PLA interface and a compatibilization effect was seen, while hBN nanoplatelets were selectively localized in the PCL phase . According to the calculated wettability coefficient, the TiO 2 has a thermodynamic preference for the PLA phase, and the hBN has a preference for the PCL/PLA interface .…”
Section: Resultsmentioning
confidence: 86%
See 4 more Smart Citations
“…In our previous studies with ternary systems, we observed that TiO 2 was selectively localized at the PCL/PLA interface and a compatibilization effect was seen, while hBN nanoplatelets were selectively localized in the PCL phase . According to the calculated wettability coefficient, the TiO 2 has a thermodynamic preference for the PLA phase, and the hBN has a preference for the PCL/PLA interface .…”
Section: Resultsmentioning
confidence: 86%
“…According to the calculated wettability coefficient, the TiO 2 has a thermodynamic preference for the PLA phase, and the hBN has a preference for the PCL/PLA interface . However, since the polymers' melting points largely differ, 59 °C for the PCL and 168 °C for the PLA, as well as their viscosities, 43 Pa s for the PLA and 3 Pa s for the PCL (the capillary rheometer curve is shown in Supporting Information Section S1), and since all blend components were simultaneously added into the extruder, the TiO 2 or the hBN were expected to be first localized in the PCL phase, and, through the driving force generated by the thermodynamic preference, they would migrate to the PLA phase or to the interface, respectively. Such behavior can be related to the nanoparticle's geometry, which hinders the migration through the interface .…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations